2021
DOI: 10.3390/microorganisms9112221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guidelines Publication on Acute Bronchiolitis Management: 10-Year Experience from a Tertiary Care Center in Italy

Abstract: Bronchiolitis is the most common lower respiratory tract infection in infants. According to evidence-based guidelines, diagnosis is clinical, there is no need for routine use of laboratory or instrumental tests and therapy is primarily supportive, based on oxygen and adequate fluid supplementation. Nevertheless, unnecessary diagnostic tests and pharmacological treatments are still very common. The aim of this retrospective cohort study was to evaluate how the management of bronchiolitis has changed in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
2
5
1
Order By: Relevance
“…Our results are completely in line with those reported by Barbieri et al evaluating the impact of the guidelines on clinical practice in Italian pediatric primary care 18 as well as with those from the study held by Biagi et al in a tertiary care center in Bologna, Italy. 19 Nevertheless, differently from our study, in the latter they found a reduction in antibiotics use (59.5% vs. 42.3%). Moreover, while they reported a significant reduction in the average length of hospitalization (5.5 vs. 4.0 days, p < 0.001), in our study such parameter did not significantly change over time (7.0 vs 6.4 days, p = 0.0649).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our results are completely in line with those reported by Barbieri et al evaluating the impact of the guidelines on clinical practice in Italian pediatric primary care 18 as well as with those from the study held by Biagi et al in a tertiary care center in Bologna, Italy. 19 Nevertheless, differently from our study, in the latter they found a reduction in antibiotics use (59.5% vs. 42.3%). Moreover, while they reported a significant reduction in the average length of hospitalization (5.5 vs. 4.0 days, p < 0.001), in our study such parameter did not significantly change over time (7.0 vs 6.4 days, p = 0.0649).…”
Section: Discussioncontrasting
confidence: 94%
“…Our data shows that the publication and spread of the national guidelines on bronchiolitis contributed to modifying clinical practice in hospitalized children with bronchiolitis in our Unit, with significant reduction in the use of chest X‐rays, blood testing and inhaled or systemic corticosteroids, while no difference was found in the use of antibiotics and of inhaled β2 agonists. Our results are completely in line with those reported by Barbieri et al evaluating the impact of the guidelines on clinical practice in Italian pediatric primary care 18 as well as with those from the study held by Biagi et al in a tertiary care center in Bologna, Italy 19 . Nevertheless, differently from our study, in the latter they found a reduction in antibiotics use (59.5% vs. 42.3%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In conclusion, in our study of 214 children with bronchiolitis diagnosed and treated in four pediatric Italian centers, we observed a favorable prognosis in all cases, with requirement of ICU limited to a minority of patients. These findings are in keeping with those reported in a contemporary, comparable, multicenter setting in Italy [ 36 , 37 ]. The vast majority of children was treated in the pediatric wards, equipped with low-flow and high-flow nasal cannula for oxygen therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The implementation of clinical practice guidelines has been reported to result in reductions in diagnostic and therapeutic resource use [ 18 ]; nonetheless, many children continue to undergo unnecessary tests and no evidence-based therapies [ 19 , 20 ]. According to this, in a previous study we have evaluated the impact of the Italian guidelines on the management of bronchiolitis in our Tertiary Care Center [ 20 ]. This study revealed that further efforts are needed to limit the prescription of ineffective therapies, particularly antibiotics.…”
Section: Introductionmentioning
confidence: 99%